Synergistic effect of nanosheet structure and carbon coating engineering to enhance lithium storage performance of molybdenum niobium oxides. (November 2022) - Deng, Z.; Wei, Q.; Wan, G.; Zhao, G.; Shi, S.; Mou, P.; Teng, S.; Du, C.; Wang, G.
Abstract: Improving the conductivity of electrode materials and the migration rate of lithium-ions in the working process, and keeping the structure of the battery stable in the charging and discharging process are the key to preparing higher capacity and safer lithium-ion batteries. In this work, a novel morphology of carbon-coated MoNb12 O33 (MNO) nanosheet was successfully synthesized by precisely regulating the concentration, and combining the solvothermal method and the high temperature calcination treatment. The unique porous nanosheet structure is more favorable for shortening the ion transport distance between electrode and electrolyte than MNO with other morphological structures due to its larger contact area. In addition, the carbon shell can interconnect MNO particles into a conductive network that improves the conductivity of composites as well as serve as an armor that maintains the structure stable during the electrochemical behavior. Consequently, the initial coulombic efficiency of the flaky MNO coated with carbon (F-MNO@C) is 96.29%, and the specific capacity can be maintained at 144.23 mA h/g after 1000 cycles test at 10 C, which is still higher than 88.75 mA h/g of the pristine MNO (F-MNO). Graphical abstract: Image 1 Highlights: MoNb12 O33 with a relatively uniform sheet-like morphology was synthesized. A thin carbon layer was coated on the surface of MoNb12 O33 to form a continuous conductive network. MoNb12 O33 @C exhibited an extremely fast Li-ion diffusion coefficient. The MoNb12 O33 @C maintained a specific capacity of 144.23 mA h/g after 1000 cycles at 10 C.